تأثير برنامج إعادة التأهيل القلبي على فعالية الوظيفة القلبية للمرضى البالغين بعد احتشاء العضلة القلبية في المرحلة ما بعد الحادة - حيدر, مازن; معروف, باسم; صالح, بشرى (Latakia University Journal -Medical Sciences Series, 2018)
Myocardial infarction occurs due to blockage of a coronary artery leading to complete damage or death of a part of the myocardium. Myocardial infarction leads to diastole and systole dysfunction that may develop into the clinical syndrome known as heart failure. Coronary rehabilitation of a range of therapeutic measures is particularly beneficial and effective in patients with coronary artery disease. In this study, 30 patients were divided into two groups (control and experimental), each group of 15 patients with the aim of conducting a comparative study on the impact of the application of cardiac rehabilitation program on cardiac function. Showed an improvement in cardiac function in the experimental group which the rehabilitation program was applied compared to the control group. And recommended to approve this program for all patients admitted to the history of acute myocardial infarction. يحدث إحتشاء العضلة القلبية بسبب احتباس الدم نتيجة انسداد أحد الشرايين التاجية مما يؤدي إلى ضررٍ أو موتٍ كاملٍ لجزء من عضلة القلب، و يؤدي احتشاء العضلة القلبية إلى حدوث سوء وظيفة انقباضية و انبساطية والتي قد تتطور نحو المتلازمة السريرية المعروفة بقصور القلب، يقدم برنامج إعادة التأهيل القلبي مجموعة من التدابير العلاجية المفيدة بشكل خاص وفعالة في المرضى الذين يعانون من مرض الشريان التاجي. تم في هذا البحث دراسة 30 مريضاً وزعوا على مجموعتين ضابطة وتجريبية كل مجموعة 15 مريض بقصد إجراء دراسة مقارنة حول تأثير تطبيق برنامج إعادة التأهيل القلبي على الوظيفة القلبية. تبين تحسن في الوظيفة القلبية في المجموعة التجريبية التي طبق عليها برنامج إعادة التأهيل مقارنة بالمجموعة الضابطة. وأوصت باعتماد هذا البرنامج لجميع المرضى المقبولين بقصة احتشاء عضلة قلبية حاد.